Kebersyukuran pada Anak yang Sudah Mengetahui Statusnya sebagai Anak Adopsi - Pramesti, Verina Anggia; Arianti, Rudangta (Penerbit Goodwood, 2023)
Purpose: This study aims to determine gratitude in children who already know their status as adopted children. This study looks at whether as adopted children, they feel grateful or not while being adopted and how they view their lives Methodology/approach: This study took 2 participants with several criteria, namely female, early adult age (19 - 25 years), adopted since infancy, knowing their status as adopted children in late adolescence (13 - 18 years), knowing their status as adopted children from adoptive parents, already knowing their status as adopted children for 3-5 years. The data collection method used in this research is using semi-structured interview techniques using interview guidelines. Results/findings: The results showed that as adopted children, participants felt grateful. As adopted children they see life as a blessing from God. Although at the beginning they showed negative feelings or negative affect, over time they were able to accept reality and feel grateful as adopted children Conclusions: The study finds that adopted children who learned about their status during adolescence are able to develop gratitude over time. Limitations: This research is limited to two female participants with similar age ranges and life experiences. Contribution: This study offers insights into how adopted individuals process identity and emotional acceptance. It emphasizes the role of gratitude in coping and adjustment, and can inform adoptive families and mental health professionals about the importance of communication and emotional support following disclosure of adoption status.